Pengembangan Keterampilan Masyarakat melalui Transformasi Perpustakaan Berbasis Inklusi Sosial pada Perpusdes Lentera Desa Buluagung Karangan Trenggalek - Kamidah, Siti Nurul; Syafaah, Darisy (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
Library as a place in developing community skills in order to do transformations that suitable for people need,  one of them is for transform into  libraries based on social inclusion. This research was done in order to describe about transforming of the village library "lentera desa" into libraries based on social inclusion to increase the community skills. This study involves descriptive qualitative methods with data collection through interviews, observations, and documentation. The result of this study shows that the lentera desa library In transforming into libraries based on social inclusion with several parties, for example the departement of library and Trenggalek district archive and UMKM for create programs to the benefit of society. As for the activity programs that have carried out the lantern of the village such ast knit training, occulcer training, and dancing training. Some difficulry in applying the transformation are processing the administration of library activities that has not been done well, there is no an activity program for disability, anda lack of work in marketing of knit products.